Photogrammetric Modelling for Urban Medieval Site Mapping. A Case Study from Curtea de Argeş, Romania - Nistor, Constantin; Mihai, Bogdan; Toma, Liviu; Carlan, Irina (Quaestiones Geographicae, 2017)
Detailed mapping of urban historical sites superposed on natural landforms within built-up areas is a real challenge. Digital photogrammetric techniques meet the requirements for mapping archaeological sites within dense built-up areas. The objectives are to reveal the landform value in medieval site development and to analyse its impact on the landforms. The aim of the present study is to highlight the contribution of geomatics technologies for the evaluation and preservation of historical sites using UAV (Unmanned Aerial Vehicle) imagery and field photos for 3D modelling. Curtea de Argeş medieval site, established on Argeş River terraces and attested since the 13th century, represents the town core for which the specific methodology was applied.